A lineage of Grace : Five Stories of Unlikely Women Who Changed Eternity - Rivers, Francine, 1947- (Carol Stream, Ill. : Tyndale House Publishers, 2009)
Tamar, Rahab, Ruth, Bathsheba, Mary, five women-- all chosen by God.
Keywords: Women in the Bible -- Fiction; Christian fiction, American; Biographical fiction; Bible fiction